Pengaruh Profitabilitas, Capital Intensity, Likuiditas Dan Biaya Operasional Terhadap Pajak Penghasilan Badan Pada Perusahaan Makanan Dan Minuman Yang Terdaftar di BEI Periode 2015-2021 - Muhammad Farhan; Saparuddin Siregar; Nursantri Yanti (LPPM Universitas Labuhanbatu, 2023)
The purpose of this research is to examine and analyze the partial and simultaneous effect of profitability, capital intensity, liquidity and operational costs on corporate income tax at Food and Beverage Companies Listed on the IDX. The research approach uses associative methods with quantitative data. The population in Food and Beverages Listed on the IDX from 2015 to 2021, the sample for this study was 56 samples. The data collection technique used in this research is documentation. The analysis technique used in this research is descriptive statistics, Panel Data Multiple Linear Regression analysis using the e-views application, then hypothesis testing and Determinant testing are carried out. The results showed that Profitability and Operational Costs partially had a positive and significant effect on Corporate Income Tax, Capital Intensity partially had a negative and significant effect on Corporate Income Tax, Liquidity partially had no effect on Corporate Income Tax and simultaneously showed that profitability, capital intensity , liquidity and operational costs have a significant effect on Corporate Income Tax at Food and Beverage Companies Listed on the IDX for the 2015-2021 period.